Coercive Control in Intimate Relationships: Differences Across Age and Sex - Policastro, Christina (Journal of interpersonal violence, 2021)
Research indicates that intimate partner violence (IPV) victimization is a gendered phenomenon with a plethora of studies exploring the relationship between sex and IPV experiences. The literature, however, has primarily focused on IPV among young couples with limited attention to how abuse manifests and changes as individuals grow old. In particular, studies have not fully analyzed how coercive control experiences vary across age, as well as by sex. The current study expands upon prior work using data from the National Intimate Partner and Sexual Violence Survey (NISVS) to investigate how the effects of sex on two forms of coercive control, intimidation and surveillance, are moderated by age, while controlling for health impairment and other key demographic characteristics. The findings reveal that older persons regardless of gender are less likely to experience surveillance or intimidation. However, men compared with women are significantly more likely to report surveillance, and younger women are significantly more likely to report experiencing intimidation compared with younger men. Implications and directions for future research are presented.